Effectiveness of Design Thinking-Based Project-Based Learning Model on Senior High School Students’ Numeracy Skills - Rizqiya A'izzatul Khusniyah; Ida Dwijayanti; Aryo Andri Nugroho (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2026)
This study aims to examine the effect of Project-Based Learning integrated with a Design Thinking approach on senior high school students’ numeracy skills in statistics. Although Project-Based Learning has been widely studied in mathematics education, most studies focus on general outcomes such as problem-solving, while research specifically addressing numeracy skills in statistics and its integration with Design Thinking remains limited. This study employed a quasi-experimental design using a posttest-only control group involving experimental and control classes. The sample consisted of eleventh-grade students selected through a non-random sampling technique. The instrument was a numeracy test that had been validated and tested for reliability, and the data were analyzed using ANOVA and effect size calculation. The results indicate that the mean numeracy score of the experimental group (M = 82.50) is higher than that of the control group (M = 70.94), with a statistically significant difference (p < 0.05). The effect size (Cohen’s d = 0.90) is categorized as large, indicating a strong practical significance of the observed difference. Therefore, the implementation of Project-Based Learning integrated with Design Thinking demonstrates a strong positive effect on students’ numeracy skills, supported by a large effect size.